Analisis Hukum Terhadap Pengaturan Kualifikasi Komoditi Dalam Penerapan Tarif Pada Barang Export Import (Studi Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean Belawan) - Maysarah Maysarah (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
In Article 12 paragraph (1) Law 1o Tahun 1995, stated that Duty free import of goods by its hinger maximum rate of 40% (forty percent) of the customs value for the calculation Import Duty. Application of provisions of the approval of the establishment of the world Trade Organization, as defined in the explanation UU No.10 Year 1995 Article 12 paragraph (1): Premises noticed Act No.7 of 1994 on ratification Trade Organization The World (Agreement on Establishing the World Trade Organization), its large maximum tarif in this paragraph set as high as forty percent of the said Customs Sign Rewards (BMI), and at the time of enactment legislation is still subject to barng-goods certain. in this verse is to Article 17A. To examine these research needs that are deskreptik juridical analysis of the problem examined include how the role of the Office of Surveillance and the Customs and Excise Service Associate Study Belawan in Application Rates In Export Import Goods. Data collection tool was questionnaire, interview and case examples. Secondary data dikumpulkan supported by deductive dan inductive methods and still refer to the normative juridical and sociological. The results showed that the application of Rates In Export Import very goods vital and competent. In Article 12 paragraph (1) of 1995, stated that the goods imported free of duty by its high maximum rate of 40% (forty perpect) of the value for customs duty calculation, but because of the many types and qualification the price of a particular commodity to make law. 10 of 1995 can not be applied as appropripate. It is suggested that a better Finance Minister of State and Minister of Industry and Trade Departemen implement this type of qualification rates is the stuff that is only 2 kinds of goods such as groceries ensensial community needs and luxuries.